Penerapan Algoritma C4.5 Dalam Memprediksi Tingkat Kelulusan Siswa Pada SMPN 06 Bengkulu Tengah - Wahidi, Agus Rahman; Maryaningsih, Maryaningsih; Suranti , Dewi (Jurnal Komputer, 2023)
SMPN 6 Central is a junior high school educational institution in Central Bengkulu. This school has a lot of data related to academic activities, for example student graduation data. These data have not been utilized as fully as possible, for example to predict student graduation, so that action can be taken to maximize preparation for the final exam. This research was conducted to design an application system using a classification technique that can process large amounts of data to find patterns that occur in student data. The data processing is used to predict student graduation. The classification technique used is the decision tree with the implementation of C4.5 algorithm. The input used is in the form of attributes from student data including semester from semester 1 to 6, skills scores and National Standard School Examination scores (USBN). Therefore, to make it easier to predict the graduation rate, an application testing uses data on students who have graduated from 2019 to 2020, totaling 100 students and the results of testing from 2021 to 2022, totaling 81 students. The knowledge gained from the results of the application training is expected to be utilized by the management of SMPN 6 Central Bengkulu as a more effective decision-making tool in planning and preparing for students' final exams. Based on the results of the tests carried out, it can be concluded that this application can predict student graduation at SMPN 6 Central Bengkulu.